Ulcerative colitis: one disease or two? (Quantitative histological differences between distal and extensive disease). Issue 4 (April 1990) - Jenkins, D; Goodall, A; Scott, B B
Abstract : Cell counts and measurements of mucosal architecture were made on rectal biopsies from nine patients with total colitis, eight with left sided colitis, 15 with distal colitis, and 11 with proctitis. The mean total lamina propria cell count in proctitis and distal colitis approached twice that of extensive left sided and total colitis (p less than 0.001) and in distal proctocolitis the cell numbers are further increased in the chronic over the acute phase. This difference was not explained by age, duration, activity, or treatment. The predominantly increased lymphoid and mononuclear cell infiltrate in distal proctocolitis indicates a different pattern of immune response, suggesting a separate process from extensive colitis or a more intense reaction resulting in localisation of disease.